How Should Taxpayers Respond the Tax Authority Supervision? - Saptono, Prianto Budi; Khozen, Ismail (Universitas Muhammadiyah Magelang, 2021)
The Directorate General of Taxes (DGT) has adopted a compliance risk management approach to monitor taxpayers optimally. In the initial supervision process, DGT often sends a Letter of Request for Explanation of Data and Information (SP2DK) to taxpayers to ensure that their tax obligations are fulfilled. This study aims to analyze how taxpayers respond to the supervision under SP2DK to minimize disputes with tax authorities. The analysis was carried out qualitatively. This study concludes that taxpayers need to be further involved with Account Representative interactions to determine their wishes to adapt to the prevailing tax control system. Understanding how AR works can help taxpayers be better prepared for the ongoing supervisory process. However, taxpayers also need a deeper understanding of tax knowledge, especially about supervision, to adjust to the data and explanation requested by AR. Direktorat Jenderal Pajak (DJP) menerapkan pendekatan manajemen risiko kepatuhan untuk memantau Wajib Pajak (WP) secara optimal. Dalam proses pengawasan awal, DJP kerap mengirimkan Surat Permintaan Penjelasan Data dan/atau Informasi (SP2DK) kepada WP untuk memastikan terpenuhinya kewajiban perpajakannya. Penelitian ini bertujuan untuk menganalisis bagaimana WP menanggapi pengawasan di bawah SP2DK untuk meminimalkan sengketa dengan otoritas pajak. Analisis dilakukan secara kualitatif. Studi ini menyimpulkan bahwa WP perlu terlibat lebih jauh dalam berinteraksi dengan Account Representative (AR) untuk mengetahui keinginannya beradaptasi dengan sistem pengendalian pajak yang berlaku. Memahami bagaimana AR bekerja dapat membantu WP lebih siap untuk proses pengawasan yang sedang berlangsung. Namun wajib pajak juga membutuhkan pemahaman yang lebih dalam tentang perpajakan, khususnya tentang pengawasan, untuk menyesuaikan dengan data dan penjelasan yang diminta oleh AR.